Retracted: Application and Practice of VR Virtual Education Platform in Improving the Quality and Ability of College Students - Qian Zhang; Ke Wang; Sheng Zhou (IEEE Access)
The competition among countries in the world is becoming more and more fierce, among which the most important is the talent competition with core competence. Therefore, it is a top priority for the world education to cultivate talents who can master the core competence in line with the world development trend. The purpose of this study is to make a beneficial practice for the application of virtual reality technology in students’ education and for the teaching points at this stage, so as to open up the ideas for further research. Based on VR virtual education platform, this paper first introduces the current research status, some important concepts of virtual reality technology, and clarifies the importance of education and some disadvantages under the traditional education mode. Then, through the collected literature and survey data, the feasibility of combining virtual reality technology with education is analyzed to provide theoretical basis. The subjects were selected from a key university in our city, and the questionnaire survey was conducted among freshmen to juniors by random sampling. The survey of quality education activities in colleges and universities, the survey of students’ favorite education methods, the survey of virtual education platform curriculum arrangement and the comparison of quality and ability were carried out. The experimental results show that the traditional course learning is still the main mode of quality-oriented education in Colleges and universities, but lectures, publicity and social practice are also used to educate students, but the proportion is not very high. All three-degree pupils tend towards the traditional way of school education, which represents more than fifty%. The proportion of young students is the highest of the three grades, which corresponds to 62.3%.In addition, the quality and ability of students improved significantly after learning the virtual learning platform.